Accidental dural puncture during labor analgesia and obstetric outcomes in nulliparous women. (May 2019) - Shea, K.; Choi, L.; Jagannathan, D.; Elterman, K.; Robinson, J.; Kodali, B.; Huang, C.C.; Palanisamy, A.
Highlights: The impact of accidental dural puncture on obstetric outcomes is unknown. We performed a retrospective cohort study to address this knowledge gap. Nulliparous women with accidental dural puncture were compared to those without. Accidental dural puncture was associated with prolonged second stage of labor. There was no apparent effect on instrumented or cesarean delivery rates. Abstract: Background: The effect of accidental dural puncture during labor epidural analgesia on obstetric outcomes remains unexplored. In this retrospective cohort study, we tested the hypothesis that accidental dural puncture is associated with prolonged second stage of labor. Methods: Anesthetic and obstetric data from nulliparous parturients who suffered an accidental dural puncture at term labor (n=89) during the years 2006–2012 were compared with randomly selected parturients with uncomplicated epidural analgesia (n=232). The primary outcome was the proportion of parturients with prolonged second stage of labor: secondary outcomes were the proportion of instrumented and cesarean deliveries. Statistical analysis included student t-test for continuous variables, chi-square test for binary variables, and logistic regressions for associations between accidental dural puncture and outcomes. Results: Demographic and obstetric characteristics of parturients were comparable except for a non-significant increase in prolonged second stage of labor in the accidental dural puncture group (27% vs. 17%, P =0.06). After adjusting for known potential confounders, multivariate logistic regression analyses revealed a significant association between accidental dural puncture and prolonged second stage of labor (adjusted risk ratio [aRR] 1.99, 95% CI 1.04 to 3.82; P =0.037). This was not accompanied by an increase in instrumented (aRR 0.57, 95% CI 0.27 to 1.21; P =0.15) or cesarean delivery (aRR 1.83, 95% CI 0.89 to 3.77; P =0.10). Conclusion: Accidental dural puncture during labor analgesia was associated with prolonged second stage of labor in nulliparous parturients. Prospective studies are needed to assess the relationship between the quality of neuraxial block after accidental dural puncture and obstetric outcomes.